Psychoanalytic Discourse of the 1920s-1930s Ukrainian Novellas - Maftyn, Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article highlights the impact of Freud’s ideas on the Ukrainian prose between the Two World Wars. The analysis of the works by V. Pidmohylnyi and I. Cherniava shows that in literary texts, the erotic-death paradigm is one of the ‘modernist’ algorithms for plot development; in the novellas, this paradigm affects the process of conflict modeling and conflict development. It is rightly believed that V. Pidmohylnyi’s dominant literary interest was the ‘helplessness of human morality before the temptations of crime’. In the novella analyzed in this study, Pidmohylnyi adopts the perspective of the ontogenesis of the human soul at the age of puberty. I. Cherniava explores the theme of subconscious ‘temptation of crime’ a wicked and thoughtless children’s game is sure to unleash. The two stories have many features in common: they are thematically close; in both of them, the plot is based on the Freudian ideas; stylistically, they are realist-oriented works with certain elements of naturalism. The novellas belong to the same type of structurally modified literary works, in which the action is no more important than the resultant psychic changes in the characters. In both novellas, the plot is built around stable structural-behavioural patterns of human culture (in Vania, it is the initiation trial pattern; in The Execution, the perverse play pattern, the game of a trial transformed into a crime). Both works have rather specific expositions, which fulfill the function of ‘Vorgeschichte’ – they tell a reader about certain psychic inclinations of the characters and present the projection of the central theme. In both novellas, the plot type, which determines the development of action, is outlined in the prehistory. Structurally, the two novellas are based on parallelism of events. As to their style, both works bear the features of naturalism